A arte-spray de Banksy : grafite e videografia - Estevão, Gustavo Russo (Universidade Federal de São Carlos, 2016)
This research aims to investigate the mechanisms of creation and production by the British artist Banksy, the leading exponent of what became known as Street Art in the early 2000. It starts with his incursion as an audiovisual director of the work launched in 2010 Exit Through the Gift Shop to discuss the relations between the street artist and the documentary filmmaker. From the constitutive elements of the filmic text it is noticed various mirroring of the processes initiated by the artist: appropriation and subversion of cultural texts, parodying and social criticism. Initially it discusses the film from the perspective of some film theories (markedly the documentary film) and other film genres. Following it draws up an overview of the genesis of Street Art and its reception and finally it shows the intersection and dialogue between the street artist and the documentary filmmaker based on the proposals of Julio Plaza and the Intersemiotic Translation.
Keywords: Teorias do documentário; Arte de rua; Banksy; Arte-spray; Documentary Theory; Street Art; Banksy; Spray Art; LINGUISTICA, LETRAS E ARTES::ARTES